2013
DOI: 10.3901/cjme.2013.06.1149
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of residual stresses in micro-arc oxidation ceramic coatings on 6061 Al alloy

Abstract: Most researches on micro-arc oxidation mainly focus on the application rather than discovering the evolution of residual stresses. However, residual stresses in the surface coatings of structural components have adverse effects on their properties, such as fatigue life, dimensional stability and corrosion resistance, etc. The micro-arc oxidation ceramic coatings are produced on the surfaces of 6061 aluminum alloy by a homemade asymmetric AC type of micro-arc oxidation equipment of 20 kW. A constant current den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In fact, there have been several reports [102][103][104][105][106] of high measured residual stress levels (>∼400 MPa) in PEO coatings, although there are also very wide variations in the results. However, these were all obtained using measured shifts of X-ray diffraction peaks.…”
Section: Residual Stress Levelsmentioning
confidence: 99%
“…In fact, there have been several reports [102][103][104][105][106] of high measured residual stress levels (>∼400 MPa) in PEO coatings, although there are also very wide variations in the results. However, these were all obtained using measured shifts of X-ray diffraction peaks.…”
Section: Residual Stress Levelsmentioning
confidence: 99%
“…Nevertheless, all these phases exhibit a significantly higher hardness compared to the substrate [12][13][14] and also compared to oxide coatings produced by anodising or hard-anodising. The high hardness, residual compressive stresses in the oxide coating [15], and the compact microstructure of the oxide coatings produced by PEO lead to a high wear resistance [12,16,17]. Since the oxide is chemically stable and its morphology is often compact, corrosion resistance is also enhanced [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…22,45,55 It was found that the use of ultrasound on aluminum alloy increased the thickness of MAO coatings and favored phase transformation from γ-Al 2 O 3 to α-Al 2 O 3 . 54 In the case of Ti-6Al-4 V, it was noted that the US influenced the morphology, phase composition, wear resistance, and corrosion properties of MAO coatings. 56 This is related not only to the use of ultrasound but also to the electrolyte components and process parameters.…”
Section: Introductionmentioning
confidence: 99%